2014
DOI: 10.2169/internalmedicine.53.2783
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Mucinous Adenocarcinoma Mimicking Organizing Pneumonia Associated with <i>Mycobacterium fortuitum</i> Infection

Abstract: We herein report the case of a 68-year-old man diagnosed with invasive mucinous adenocarcinoma of the lungs. Chest computed tomography showed subpleural ground-glass opacity and small nodules with cavitation. A culture of the bronchoalveolar lavage fluid resulted in the detection of Mycobacterium fortuitum. The patient's lung consolidation rapidly progressed; however, repeated bronchoscopy showed no atypical cells, thus suggesting a diagnosis of organizing pneumonia associated with M. fortuitum infection. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Although the clinical presentation may show non-cavitary alterations, cases with cavitary lesions tend to have a poor prognosis due to complications and the rapid deterioration of patients, as we reported in this case, coinciding with other previous reports [7,12]. Upon patient admission, an infectious process associated with tuberculosis or pneumonia was considered due to the radiological characteristics, as has been reported in IMA with mycobacterium fortuitum infection [13]. It is important to consider IMA with cavitary radiologic features as part of the differential diagnosis.…”
Section: Discussionsupporting
confidence: 87%
“…Although the clinical presentation may show non-cavitary alterations, cases with cavitary lesions tend to have a poor prognosis due to complications and the rapid deterioration of patients, as we reported in this case, coinciding with other previous reports [7,12]. Upon patient admission, an infectious process associated with tuberculosis or pneumonia was considered due to the radiological characteristics, as has been reported in IMA with mycobacterium fortuitum infection [13]. It is important to consider IMA with cavitary radiologic features as part of the differential diagnosis.…”
Section: Discussionsupporting
confidence: 87%
“…He was diagnosed with organizing pneumonia associated with Mycobacterium fortuitum infection by the BLAF culture. However, the surgical biopsy specimen was diagnostic for IMA, with no mycobacterial infection [8]. Beom et al reported a case of a 64-year-old woman with a six-month history of cough, febrile sensation, and shortness of breath.…”
Section: Discussionmentioning
confidence: 99%
“…Further, not only bacterial pneumonia but other diseases such as fungal infection, organizing pneumonia, and even consolidative lymphoma might mimic invasive mucinous adenocarcinoma. [3; 21] Prospective studies that focus on margin information in various pulmonary diseases are needed and we speculate that this margin analysis method could be applied to other diseases to differentiate cancer and mimickers.…”
Section: Discussionmentioning
confidence: 99%